Immunohistochemical distribution of androgen receptor in rat testis during postnatal development - Timurkaan, S.; Gur, F. M.; Karan, M. (Ecole Nationale Veterinaire Toulouse, 2012)
Androgens are essential for the maintenance of normal spermatogenesis and postnatal differentiation of the testis. The AR expression in testis was evaluated by immunohistochemistry in 14-90 days old rats (n = 15). No reactivity was seen in the nucleus or the cytoplasm of germ cells. Positive AR immunostaining was detected in the nuclei of testicular somatic cells such as peritubular myoid cells, Sertoli cells, and Leydig cells. Although AR immunolabelling was important and constant in myoid cells, it progressively increased in Sertoli and Leydig cells but declined in the Leydig cells since the 35(th) day. These results are consistent with the interpretation that androgen regulation of spermatogenesis occurs solely via somatic cells.
Keywords: Androgen receptor; immunohistochemistry; testis; rat; Sertoli cell; Leydig cell; myoid cell; germ cell